Legal Protection of Intellectual Property (Copyright) of Creative Economy Actors: Medan City Government Program Study - Widianto, Bayu; Paulen, Paulen (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
One important aspect in the development of the creative economy is the legal protection of copyright. Copyright is a very valuable intangible asset, especially for creative economy actors who depend on the originality of the work as a source of income. Copyright protection not only provides legal certainty, but also encourages the creation of a healthy and sustainable business climate. However, there are still many creative economy actors who do not understand the importance of copyright registration, making their works vulnerable to piracy and claims by other parties. Based on data from the Directorate General of Intellectual Property of the Ministry of Law and Human Rights, the level of copyright registration in Indonesia is still relatively low when compared to the potential of creative works produced every year. This research uses a normative-empirical juridical approach and is descriptive in nature. The data used consists of primary and secondary data. Primary data is obtained through interviews and observations of creative economy actors, while secondary data is collected through documentation studies. The analysis technique used is qualitative, because most of the data obtained is narrative in nature. This study aims to analyze the implementation of copyright protection for creative economic actors and the obstacles faced in the registration process.